HOW TO MINIMIZE THE BLEEDING RISK IN PATIENTS WITH ATRIAL FIBRILLATION UNDERGOING PERCUTANEOUS CORONARY INTERVENTIONS: LESSONS DRAWN FROM RANDOMIZED TRIALS AND NEW CLINICAL GUIDELINES - O. O. Shakhmatova; Е. P. Panchenko («REMEDIUM GROUP» Ltd., 2018)
In the current practice, patients with atrial fibrillation receive triple antithrombotic therapy after PCI, which includes aspirin, clopidogrel and oral anticoagulant. Several clinical trials were conducted to identify an alternative strategy for antithrombotic therapy that would minimize the risk of haemorrhagic complications, including RE-DUAL PCI trial, in which the treatment regimens under test have been developed in accordance with the current guideline recommendations and requirements of real clinical practice. This trial compared the standard triple antithrombotic therapy - warfarin, P2Y12 receptor inhibitor for 12 months and aspirin (≤100 mg) for 1-3 months - and two regimens of dual antithrombotic therapy including a P2Y12 receptor inhibitor and dabigatran at one of the doses recommended to prevent stroke - 110 mg twice daily or 150 mg twice daily (for 12 months). The rates of major bleeding events in the 110 mg DE-DAT treatment arm were significantly lower as compared with the standard therapy, and the frequency of major ischemic events was insignificantly higher. In the 110 mg DE-DAT treatment arm, the rates of major bleeding events were also significantly lower, and an insignificant tendency towards reduction of ischemic events was also revealed. Thus, both regimens are equally effective, but potentially safer compared with the standard therapy, so if a particular patient has different risk ratios of ischemic and haemorrhagic events, the physician may choose the more preferable. The article also discusses practical approaches to minimizing the risk of bleeding in patients with AF who receive combined antithrombotic therapy after PCI.